Predicting Factors of Happiness at Work of Faculty Staffs of Boromarajonani College of Nursing Nakhon Phanom, Nakhon Phanom University - Kempanya, Pipatpong; Reungsuksud, Piches; Prommasakha Na Sakonnakhon, Nuttiya; Koteprom, Jarintorn; Intharakasem, Sirirat; Summart, Ueamporn (Journal of The Royal Thai Army Nurses, 2023)
The objectives of this study were to identify happiness and factors predicting happiness towards working among faculty staff of Boromarajonani College of Nursing Nakhon Phanom, Nakhon Phanom University. The sample consisted of 90 staffs. Data were retrieved by self-administered questionnaires including baseline characteristics and the happiness self-assessment questionnaire (Happinometer). Descriptive Statistics was used to describe happiness level and multiple logistic regression was performed to investigate the relationship between various factors and happiness. The overall prediction property of the final model was also examined using receiver operating characteristics (ROC) curve. The results showed that the sample group had an overall score of happiness level at 74.6 points which was identified as happy. The mean score of overall happiness was (3.7±SD = 0.4; 74.65%. According to the dimension of happiness, the sample had the highest mean score in the happy family dimension (4.1±0.5; 81.8%) and the lowest score in happy money dimension (3.2±0.8; 64.0%). In addition, factors that significantly predict the happiness at work among faculty staffs were being respected 8.62 (95%CI:1.81-41.08; p = 0.007), and affecting morale 2.48 (95%CI :1.02-6.16; p = 0.050). The area under ROC curve of this final model was 72.77%. The findings suggest that board of Boromarajonani College of Nursing Nakhon Phanom should support and plan to create happiness projects for staff in the financial dimension and develop factors concerning with being respected and affecting morale that will make the staffs having more happiness.